Roles of cataloguing librarians in the digital era. Issue 6 (2nd September 2019) - Al Hijji, Khalfan Zahran; Al-Busaidi, Mohammad Khamis
Abstract : Purpose: This study aims to explore the roles and skills of Omani academic cataloguing librarians in facilitating access to various kinds of traditional and digital information resources and challenges confronting them in fulfilling that task. Design/methodology/approach: Data for this research were gathered from 37 academic libraries in the country through a questionnaire sent to their cataloguing librarians. Google Docs format was used for cumulating and presenting quantitative data, whilst content analysis was utilized for gathering the qualitative data in specific themes according to the research questions. Findings: The obvious findings are that Omani academic cataloguers still perform the traditional cataloguing functions, including copy and original cataloguing, and maintain authority files. Moreover, more than half of the respondents have the skills required for working in groups and are familiar with cataloguing tools such as RDA rules and BIBFRAME. However, cataloguers lack familiarity with computer languages (XML, PMH, OAI, RDF) and metadata. Practical implications: The research concludes with suggestions to libraries for improving librarians' skills and performance through such as provision of proficient training and establishment of a collaborative body. Originality/value: This research addresses an area of interest to most librarians. However, few researchers in the authors' region have focused on this topic. The study, therefore, aims to contribute to filling this gap through assessing whether cataloguers in Oman have the skills and roles required for organizing various information resources in the digital era.